The emperor's egg - Jenkins, Martin; Chapman, Jane, 1970- (Cambridge, Mass. : Candlewick Press, 1999)
Describes the parental behavior of Emperor penguins, focusing on how the male keeps the egg warm until it hatches and how the parents care for the chick after it is born.
Keywords: Emperor penguin -- Behavior -- Juvenile literature; Parental behavior in animals -- Juvenile literature; Emperor penguin -- Habits and behavior; Penguins -- Habits and behavior; Parental behavior in animals